2008
DOI: 10.1177/156482650802900202
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Nutrition Security with Treatment of People Living with HIV: Lessons from Kenya

Abstract: These findings provide further empirical support to calls for a more holistic and comprehensive response to the coexistence of AIDS epidemics with chronic nutrition insecurity. Future work is needed to clarify ways of bridging the gap between short-term nutritional support to individuals and longer-term livelihood security programming for communities affected by AIDS. Such interdisciplinary research will need to be matched by intersectoral action on the part of the agriculture and health sectors in such enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 12 publications
(11 reference statements)
1
81
1
1
Order By: Relevance
“…The majority (61 %) of clients reported that, as a result of the food supplementation, they regained enough strength to return to their household chores, farming activities, or income-earning activities. The amount of labor available in their household increased as the patient recuperated [62]. In the 12-month prospective TASO-RENEWAL study, food assistance increased household food security, but not individual dietary diversity: Household Food Insecurity Access Score increased by 2.1 points [61].…”
Section: Safety Nets Targeted To Hiv-affected Householdsmentioning
confidence: 93%
“…The majority (61 %) of clients reported that, as a result of the food supplementation, they regained enough strength to return to their household chores, farming activities, or income-earning activities. The amount of labor available in their household increased as the patient recuperated [62]. In the 12-month prospective TASO-RENEWAL study, food assistance increased household food security, but not individual dietary diversity: Household Food Insecurity Access Score increased by 2.1 points [61].…”
Section: Safety Nets Targeted To Hiv-affected Householdsmentioning
confidence: 93%
“…Previous qualitative work in Kenya 36 and other African settings have indicated that food insecurity may be a barrier to adherence. Baseline food insecurity was a strong predictor of poor adherence among people attending HIV clinics in rural Zambia.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional intervention, leading to food security of patients receiving antiretroviral therapy, has increased medication adherence, fewer side effects, weight gain, and recovery of physical and work strength of the patients and their families 15 . The serious consequences of food insecurity in relation to HIV/ AIDS reported in several studies and their prevalence observed in this study indicate that food security should be an important component of HIV/AIDS treatment programs in Brazil.…”
Section: Conflict Of Interestmentioning
confidence: 99%